Sande's HIV/AIDS medicine medical management of AIDS 2013 - Volberding, Paul; Sande, Merle A. 1939-2007 (Elsevier Saunders, 2012)
Access the latest information available in the challenging area of HIV/AIDS management with this 2nd Edition. Authored by a veritable "who's who" of current global experts in the field, this medical reference book will provide you with all the practical, indispensable guidance you'll need to offer your patients the best possible care. Access reliable, up-to-the-minute guidance that addresses the realities of HIV/AIDS management in your geographical region, thanks to contributions from a global cast of renowned expert clinicians and researchers. Locate the clinically actionable information you need quickly with an organization that mirrors the current state of the AIDS epidemic and the different needs of Western vs. developing-world patients and clinicians. Get the most relevant information available on pediatric HIV and AIDS issues; anti-retroviral drugs, including integrase inhibitors; and the use of second- and third-line anti-retroviral drugs in resource-poor settings. Stay current on the latest actionable information, such as using antiretroviral therapy in patients with tuberculosis and drug-resistant tuberculosis; antiretroviral therapy; immune reconstitution inflammatory syndromes (IRIS); and implementation of the HPV vaccine.